2006
DOI: 10.1111/j.1542-4758.2006.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac response to hemodialysis with different cardiovascular tolerance: Heart rate variability and QT interval analysis

Abstract: A therapy-specific worsening of cardiovascular stability during bicarbonate dialysis (BD) with respect to acetate-free biofiltration (AFB) have been previously reported. We further investigated the impact of the 2 therapies on electrocardiographic parameters in order to gain novel insight into the cardiac responses. Holter ECG acquired during hypotension-free sessions (12 BD + 12 AFB) were retrospectively analyzed. R-R intervals were extracted from ECG recordings. An autoregressive spectral technique was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Furthermore, the regimen employed in hemodialysis may also play a role in depicting the ‘final scene’ of ventricular repolarization. In this regard, one comparative study reported that bicarbonate dialysis reduces the QT and QTc intervals duration more than acetate-free biofiltration [17]. Since nitric oxide is produced more with the former dialysis regimen as compared with the latter [20], the authors suggested a possible role of nitric oxide in shortening the post-dialysis QT and QTc intervals duration in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the regimen employed in hemodialysis may also play a role in depicting the ‘final scene’ of ventricular repolarization. In this regard, one comparative study reported that bicarbonate dialysis reduces the QT and QTc intervals duration more than acetate-free biofiltration [17]. Since nitric oxide is produced more with the former dialysis regimen as compared with the latter [20], the authors suggested a possible role of nitric oxide in shortening the post-dialysis QT and QTc intervals duration in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it has long been believed that a dialysis-induced prolongation of the QTc interval duration – and increase of the QTD – was responsible for lethal ventricular arrhythmias during and immediately following hemodialysis, some emerging evidence suggests a decrease – rather than increase – of the QT and/or QTc interval after dialysis [17, 18, 19]. Patients with end-stage renal disease are a heterogeneous population in which a complex interplay of many factors determines the response of the QTc interval to hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the studies on HRV in ESRD patients are mainly focused on cardiac death stratification [34], to compare unstable and stable patients on HD [35,36] or to compare different type of treatment [37]. All these studies showed that a reduced HRV is an independent prognostic value of mortality and that HRV analysis permits to identify alterations in autonomic control, such in unstable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, acetate activates the massive release of nitric oxide (NO) by stimulating the synthesis of inducible NO synthase, which causes vasodilatation. The clinical manifestation of the accumulation of acetate in blood is a decrease in arterial pressure and an increase in heart rate .…”
Section: Discussionmentioning
confidence: 99%